Meaning of the Mission to Serve Children with Special Needs by Nuns: A Narrative Review - Yulia E. M. Beribe; Juliana Marlin Y. Benu; Indra Yohanes Kiling (Universitas Nusa Cendana, 2021)
This narrative review aims to discuss theories related to how nuns perceive meaning of their mission to serve children with special needs. Nun is a woman who offers herself and her life to God through the utterance of a promise/vows to carry out her mission through the ministry received from a tarekat / congregation in accordance with spirituality and the statutes of religious life. One of the nuns' missions is to serve children with special needs who have abnormalities or deviations from normal conditions in their growth and development, both psychologically, physically, socially, and emotionally, which hinder activities and interactions. Nuns serve children with special needs by seeking, nurturing, caring for, educating and living together, caring for, and meeting all the needs of children with special needs who are served as in the life of a family. Nuns interpret the duty of service to children with special needs in two complete dimensions, namely the vertical and horizontal dimensions. In addition, nuns interpret this service as a life calling from God so that it becomes a motivation for them to carry out their service duties and bring happiness.